THE EFFECT OF TEMPERATURE VARIATION AND VARIOUS METAL MATERIALS ON CONDUCTION HEAT TRANSFER RATE - Handini Novita Sari; Ika Nurjannah; I Made Arsana; Ghaniy Amirul Dana; Moch. Variant Julianto (Media Mesin: Majalah Teknik Mesin, 2023)
Thermal conductivity is the value of a material's ability to conduct heat. Heat transfer occurs due to the difference in temperature found in an object. Heat transfer can take place in three ways, namely conduction, radiation and convection. The purpose of this study was to determine the conduction heat transfer rate for 3 solid cylindrical materials, namely aluminum, iron, and brass. by varying the temperature 50 ℃, 55 ℃, 60 ℃, 65 ℃, 70 ℃, 75 ℃ and 80 ℃. The working principle in this experiment is to prepare 3 variations of solid cylinders, then place them on a thermal conduction trainer by adjusting the temperature of the test on the thermocontrol display (T1) in stages and the test results are obtained as shown by a digital thermometer (T2). From the test results, the results of the heat transfer rate have been found, for the metal material that has the greatest heat transfer rate is aluminum with a heat rate value of 479.7 Watt at 80 ℃, the second largest heat transfer rate value is aluminum with a heat transfer rate of heat is 299.7 Watt at 80℃ while for the material the smallest rate is found in iron material with a value of 214 Watt at 80℃. The average heat transfer rate for aluminum is 325.5 Watt, for an average heat transfer rate for iron is 147.1 Watt, and the average heat transfer rate of brass is 218.5 Watt.